Sabun Minyak Jelantah Ekstrak Daun Teh Hijau (Camellia sinensis) Pembasmi Staphylococcus aureus - Erna Widyasari; Farhan Dhio Yanuarsyah; Rifqi Nur Alwan Adinata (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
Used cooking oil consumption causes cancer and the waste can pollute the environment. For that cases we need to find technology to change the oil become something useful like soap. The research aims to know the procedure to make soap from used cooking oil and Camellia sinensis extract and towards the growth of bacteria Staphylococcus aureus. There are two steps to purify the oil, purify with active carbon and banana peel. It was indicated by the formation of inhibition zones with the diameter occurred Cammelia sinensis extract with the size 12,5 mm, while the used cooking oil soap Cammelia sinensis extract 11 mm, alcohol 70% 5 mm, and tetrasiklin disc 15,8 mm. The conclusion are used cooking oil Cammelia sinensis extract can be modified into soap and soap from used cooking oil Camellia sinensis extract inhibited the growth of bacteria Staphylococcus aureus.